Relationship between allograft perfusion preparation variations and rate of arterial and biliary complications in orthotopic liver transplantation - V. V. Borovik; I. I. Tileubergenov; A. V. Moiseenko; D. N. Maystrenko; D. A. Granov (Вестник трансплантологии и искусственных органов)
Objective: to evaluate the possible influence of different graft perfusion preparation variations on the incidence of biliary and vascular complications of orthotopic liver transplantation (OLT).Materials and methods. Data on 287 full-size liver transplants from donors with brain death and beating heart were processed. There were 262 and 25 primary and repeat OLTs, respectively. Before completion of portal anastomosis formation and inclusion into systemic blood flow, the graft was perfused with hypo- (group 2) and isotonic (group 4) saline in order to minimize hemodynamic disorders.Results. There was a statistically significant difference between groups 2 and 4 in the development of late (p = 0.04) and cumulative biliary complications (p = 0.01). The presence of these complications and the perfusion type were found to be associated (Fisher’s exact test = 0.02). There were no differences in incidence of thrombosis in the studied groups.Conclusion. The conducted analysis suggests that it is inexpedient to use hypothermic solutions when preparing a liver transplant for perfusion before introducing it into systemic circulation.